Sekolah Tinggi Perikanan Di Kampar Dengan Pendekatan Arsitektur Metafora - Laras Utami Inka; Wahyu Hidayat; Pedia Aldy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
River in Kampar Regency have enormous potential for freshwater cultivation in the cultivation of ponds (fresh water) and fresh floating nets (floating nets). However, the amount of agricultural sector production has not been evenly distributed in all sub-districts. To discuss the issue Kab. Kampar as the largest producer of freshwater fish in Riau, requires high school education facilities that are requested in the fisheries sector. This supports adding and maintaining human resources with added value to the fisheries sector. As a design strategy at the Fisheries High School in Kampar using field surveys, literature studies, and comparative studies. Based on the data that has been obtained, it is then processed with the principles of metaphoric architecture so as to produce a new concept that is applied in the College of Fisheries. The use of metaphoric architecture can bring up visual characters that will be applied to the form of mass. The concept of the Fisheries High School uses a form of wood used as a fishing gear. This choice represents the link between the function of lukah as a tool for catching fish and schools as a means of taking knowledge.Keyword: Fisheries School, Metaphor Architecture, Fish Trap